試行AA Vee 圖融入三階段探究教學模式對科學教師專業成長之影響 The Influence of Integrating AA Vee Map into the Three-Staged Instruction Model of Scientific Inquiry on the Professional Development of Science Teachers - 蔡明致 Tsai, Ming-Chih; 林莞如 Lin, Wan-Ju; 葉辰楨 Yeh, Chen-Jane; 張文華 Chang, Wen-Hua; 王國華 Wang, Kuo-Hua (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2011)
本研究採用行動研究的方式，試行以AA Vee 圖的策略融入三階段探究教學模式，引導國一學生進行探究活動，並呈現此過程對教師專業成長之影響。參與者為教師研究者及任教班級之37 名國一學生。本研究試行將AA Vee 圖融入「結構式探究學習活動」、「科展文獻探究學習活動」、以及「引導式探究學習活動」的三階段探 究教學模式，而在教學模式的設計、實施、修正過程中，教師研究者更藉由「行動中的反省」，獲得個人在科學探究教學上的體會與成長。本研究資料蒐集與分析以課室觀察、學生晤談、反省日誌等質性資料為主。研究結果顯示以AA Vee 圖的策略融入三階段的探究教學模式，有助於逐步培養學生的科學探究能力；進行探究的歷程及開放程度，宜配合學生的背景知識及能力進行微調；經過行動與反思，教師研究者對科學探究教學的精神有更深入的體會、更加理解學生進行探究的能力和可能遭遇的困難、並因熟悉此探究教學模式且深入參與學生的活動，更能掌握進行探究教學的策略。基於以上結果，本研究建議，運用此種階段性實施方式，能引導嘗試運用探究教學的科學教師，協助其逐步建立探究教學的實務知識，促進教師專業成長。 By means of action research, the research tried to integrate the AA Vee map into the three-staged instruction model of scientific inquiry to guide the inquiry activities for junior high school students, and to enhance the professional development of the teacher. The participants are the teacher researcher and 37 students in his class. The three-staged instruction model of scientific inquiry were “activities of structural inquiry”, “activities of exploration of literatures of science fairs”, and “activities of guided inquiry learning”. As to the designation, practice, and modification of the instructional model, the researcher analyzed his personal understanding and growth in scientific inquiry teaching through “reflection in action”. Data collected in this research are basically qualitative data like observations in classroom, interviews with students, journals on teacher’s reflections, etc. The results from constant comparison among various data sources showed that this instruction model, integrated with AA Vee map, can gradually develop students’ scientific inquiry abilities, though the inquiry process and openness should be adjusted in accordance with students’ competences. Through actions and reflections, the teacher researcher furthered his realization on the essence of scientific inquiry teaching and comprehension on students’ abilities for inquiry and possible difficulties. The teacher researcher thus became more familiar with this instruction model, further participated into student’s activities, and had better command over the strategies of inquiry teaching. It is also suggested that, with this staged practice, science teachers can be guided to try to employ inquiry teaching and gradually establish their practical knowledge on inquiry teaching.